Star Wars. Crimson reign - Soule, Charles (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2022)
"The story that began with WAR OF THE BOUNTY HUNTERS continues in the second chapter of an epic trilogy that will reshape the Star Wars galaxy during the Age of Rebellion! The criminal organization known as the Crimson Dawn has risen--but what is their goal, and how do they plan to achieve it? And how will the Rebel Alliance and the Empire both react to this new galactic power player? Featuring the return of beloved characters, shocking twists, epic feats of the Force, and a story that will reach from the darkest underworld all the way to the Imperial Palace on Coruscant, CRIMSON REIGN is a Star Wars saga like no other!"--